AVPR1b variation and the emergence of adaptive phenotypes in Platyrrhini primates. Issue 8 (18th July 2019) - Fam, Bibiana S. O.; Reales, Guillermo; Vargas‐Pinilla, Pedro; Paré, Pamela; Viscardi, Lucas H.; Sortica, Vinicius A.; Felkl, Aline B.; de O. Franco, Álvaro; Lucion, Aldo B.; Costa‐Neto, Claudio M.; Pissinatti, Alcides; Salzano, Francisco M.; et al.
Abstract: Platyrrhini (New World monkeys, NWm) are a group of primates characterized by behavioral and reproductive traits that are otherwise uncommon among primates, including social monogamy, direct paternal care, and twin births. As a consequence, the study of Platyrrhine primates is an invaluable tool for the discovery of the genetic repertoire underlying these taxon‐specific traits. Recently, high conservation of vasopressin (AVP) sequence, in contrast with high variability of oxytocin (OXT), has been described in NWm. AVP and OXT functions are possible due to interaction with their receptors: AVPR1a, AVPR1b, AVPR2, and OXTR; and the variability in this system is associated with the traits mentioned above. Understanding the variability in the receptors is thus fundamental to understand the function and evolution of the system as a whole. Here we describe the variability of AVPR1b coding region in 20 NWm species, which is well‐known to influence behavioral traits such as aggression, anxiety, and stress control in placental mammals. Our results indicate that 4% of AVPR1b sites may be under positive selection and a significant number of sites under relaxed selective constraint. Considering the known role of AVPR1b, we suggest that some of the changes described here for the Platyrrhini may be a part of the genetic repertoire connected with the complex network of neuroendocrine mechanisms of AVP–OXT system in the modulation of the HPA axis. Thus, these changes may have promoted the emergence of social behaviors such as direct paternal care in socially monogamous species that are also characterized by small body size and twin births. Abstract : Variable protein sites in AVPR1b are associated with several reproductive traits in New World monkeys. Research Highlights: Novel data from AVPR1b receptor contribute to understanding the genetic background that enabled the emergence of adaptive phenotypes. Rare reproductive behaviors found in Platyrrhini primates were associated with variants in the AVP–OXT system. The 4% of AVPR1b sites may be under positive selection and a significant number of sites under relaxed selective constraint.